Influence of final irrigation with titanium dioxide and silver nanoparticles on the fracture resistance of endodontically treated roots - Mohamed I. Ebrahim; Fahd M. Hadhoud; Ali A. Alqarni; Shaimaa M. Al Harthi; Hassan T. Shawli (Saudi Dental Journal)
Background: Titanium dioxide (TiO2NP) and silver nanoparticles (AgNPs) have been recognized for their ability to enhance the structural integrity of dental materials. This study aimed to compare the influence of these nanoparticles on the structural resilience of treated root canals. Materials and Methods: The crowns of 75 undamaged central incisors were sectioned below the cemento-enamel junction to achieve a consistent root length of 16 mm. The root canals were prepared using K3 files up to size 40 with a 6 % taper. The specimens were then divided into five groups (n = 15), each subjected to a final irrigation protocol with one of the following solutions: normal saline, 2 % chlorhexidine (CHX), 17 % EDTA combined with 2.5 % sodium hypochlorite (NaOCl), 17 % EDTA with 0.1 % silver nanoparticles (AgNPs), and 17 % EDTA with 0.1 % titanium dioxide nanoparticles (TNPs). After obturation with gutta-percha and sealer, fracture resistance (FR) was evaluated. The data were analyzed using one-way ANOVA and Tamhane’s post hoc test (p < 0.050). Results: The lowest fracture resistance (FR) was observed in the group treated with ethylenediaminetetraacetic acid (EDTA) combined with sodium hypochlorite (NaOCl), followed by the groups irrigated with normal saline and chlorhexidine (CHX), with no statistically significant difference between the latter two groups (p > 0.05). There was also no significant difference in FR between the CHX and saline groups (p > 0.05). In contrast, irrigation with silver nanoparticles (AgNPs) and titanium dioxide nanoparticles (TNPs) resulted in significantly higher fracture resistance compared to the other solutions tested (p < 0.050). Conclusion: The fracture resistance of endodontically treated roots was significantly improved when the final irrigation sequence included AgNPs and TNPs nanoparticles. In contrast, sodium hypochlorite (NaOCl) yielded the lowest fracture resistance value.